1997
DOI: 10.1111/j.1744-618x.1997.tb00318.x
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Nursing Diagnosis in Three Australian Hospitals

Abstract: RN, CM PURPOSE. To document nursing diagnoses on nursing care plans in an Australian context where NANDA nursing diagnoses were utilized. METHODS. An audit of 298 nursing care plans at three selected hospitals by three university lecturers involved in teaching nursing diagnosis. FINDINGS. Pain was the nursing diagnosis most often documented; the majority of other diagnoses pertained to physical problems experienced by patients . CONCLUSIONS. The results of this research add to the knowledge of nursing diagnosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 3 publications
3
12
0
2
Order By: Relevance
“…This was found to be a very big challenge; even when the nurses wanted to practise what they had been taught, inadequate staff increased the patient-nurse ratio, leading to a work overload; and an inability to put the acquired knowledge into practice. These findings are similar to those of King, Chard and Elliot [15], who in their study on the utilization of nursing diagnoses in three Australian hospitals, concluded that the one main factor that affected the use of the nursing process was understaffing. Also the work of Laryea [16] on the barriers to the implementation of the nursing process found that understaffing was a contributing factor to the non-utilization of the nursing process.…”
Section: Discussionsupporting
confidence: 89%
“…This was found to be a very big challenge; even when the nurses wanted to practise what they had been taught, inadequate staff increased the patient-nurse ratio, leading to a work overload; and an inability to put the acquired knowledge into practice. These findings are similar to those of King, Chard and Elliot [15], who in their study on the utilization of nursing diagnoses in three Australian hospitals, concluded that the one main factor that affected the use of the nursing process was understaffing. Also the work of Laryea [16] on the barriers to the implementation of the nursing process found that understaffing was a contributing factor to the non-utilization of the nursing process.…”
Section: Discussionsupporting
confidence: 89%
“…It is possible that usage of NANDA and non‐NANDA diagnoses vary among countries. A survey of the use of nursing diagnoses in Australian hospitals (King, Chard, & Elliot, 1997) found that 53% were non‐NANDA diagnoses, indicating that nurses use both NANDA and non‐NANDA nursing diagnoses. In addition, various other diagnoses were devised.…”
Section: Discussionmentioning
confidence: 99%
“…1991, Kuhn 1991, Sawin & Heard 1992, Gordon & Hiltunen 1995, Gordon & Butler‐Schmidt 1997, Killen et al . 1997, King et al . 1997, Lesh 1997, Ehrenberg & Ehnfors 1999a,b) and with different patient populations (Courtens & Abu‐Saad 1998, Chambers 1986, Dapice et al .…”
Section: The Studymentioning
confidence: 99%